PENINGKATAN KOMPETENSI GURU MELALUI DIKLAT DARING MASIF DAN TERBUKA (DIDAMBA) PADA MATA DIKLAT ENGLISH FOR TEACHING SCIENCE YANG DISELENGGARAKAN OLEH PPPPTK IPA - Lili Indarti; Diding Nurdin (Jurnal Pengabdian Masyarakat Multidisiplin, 2022)
The enhancement of teacher quality is urgently needed to improve the quality of learning to be more competitive globally. The Centre for Development of Teachers and Education Personnel (CDETEP) in Science or PPPPTK IPA, a technical unit under the Ministry of Education, Culture, Research, and Technology conducted a Massive-Open-Online Training (DIDAMBA). It was an alternative solution for teachers to increase their competence and professionalism economically and time-effectively. It was openly offered to teachers and education personnel in Indonesia. It aimed to improve their skills as educators and leaders to their students and school communities. A research was carried out to find out the effectivity of DIDAMBA. The Quasi Experiment Method with one-group pretest-postest was adopted in this research. The instrument was a set of test items. The targeted samples were taken from the Course of English for Teaching Science of DIDAMBA Batch 15 and 16 with 17 teachers of each batch. From the data, It was found out that the normalized gain point of Batch 15 was 0,74 whose high effectivity and Batch 16 was 0,60 whose average effectivity. Therefore, a recommendation came up that DIDAMBA was quite effective to improve the competence of teachers and education personnel in Indonesia. More themes are suggested to develop and offer to teachers and education personnel in Indonesia to support the government efforts to empower the quality education.